Effects of Age, Gender, Bolus Volume, Bolus Viscosity, and Gustation on Swallowing Apnea Onset Relative to Lingual Bolus Propulsion Onset in Normal Adults - Hiss, Susan G.; Strauss, Monica; Treole, Kathleen; Stuart, Andrew (East Carolina University, 2004)
The purpose of this study was to ascertain the normal relation of swallowing apnea (SA) onset relative to lingual bolus propulsion along with factors that may alter this relation. Forty adults, composed of ten males and ten females in each of two age groups (i.e., 20-30 and 63-79 years) participated. SA onset was assessed during 5- and 20-ml bolus volumes of water and apple juice across three trials. The effects of age, gender, bolus volume, bolus viscosity, and gustation on SA onset relative to lingual bolus propulsion were examined. A significant interaction of age by gender by volume was found. In general, older adults initiated SA onset earlier than young adults and large boluses elicited an earlier SA onset than small boluses regardless of group. Young males demonstrated significantly later SA onset than the older males for large volumes, this difference was not observed for small volumes nor was it found between young and older females. SA onset also was assessed during 5-ml bolus volumes of thin apple juice, thick apple juice, and applesauce across three trials. A significant main effect of viscosity was found revealing that SA onset was initiated later as bolus viscosity increased. Thus, the results of this investigation provided data on the relation of SA onset relative to lingual bolus propulsion in individuals with normal swallowing and how this relation changes as a function of age, gender, bolus volume, bolus viscosity, and gustation.
SA ONSET RELATIVE TO LINGUAL BOLUS PROPULSION
Keywords: Swallowing; Dysphagia; Swallowing apnea; Age; Gender; Bolus volume; Bolus viscosity; Gustation; Deglutition disorders; Apnea; Deglutition; Deglutition Disorders; Apnea